Diagnosis of table grapes sold at retail in Pelotas - RS (Research, Society and Development, 2023)
Table grapes are among the most consumed and commercialized fruits in the world and that has increased considerably in recent years. Table grape production in Pelotas is concentrated in the summer, and the grapes that are consumed in other seasons are from other states or even countries. The present work objective is to develop a research about the main table grapes sold in the retail of Pelotas and their qualitative characteristics. In each season of the year, samples were collected from all cultivars available in four previously selected retailers were carried out, with at least 2 bunches per cultivar, in order to analyze the following variables: bunch and berry mass, bunch length, length and diameter of berry, soluble solids (SS) and titratable acidity (AT). Of the grapes sold at retail in Pelotas, the fine ones represent more than 60% in all the periods studied when compared to American and hybrid grapes. The traditional varieties Italia, Red Globe, Niagara Rosada and Benitaka, are the most commonly found. Spring was the season in which the greatest diversity of cultivars was found. New cultivars such as Arra15®, Sable Seedless® and Sweet Celebration® are slowly being introduced. Some cultivars were outside the commercialization standard, in terms of maturity and bunch size.